Think of the Children: Liability for Non-Disclosure of Information Post-Montgomery. (26th August 2019) - Cave, Emma; Purshouse, Craig
Abstract: In 2015, the Supreme Court in Montgomery v Lanarkshire Health Board handed down a landmark decision on informed consent to medical treatment, heralding a legal shift to a more patient-centred approach. Montgomery, and the extensive commentary that has followed, focuses on 'adult persons of sound mind'. Cave and Purshouse consider the potential claims that may flow from a failure to adequately inform children. They argue that the relevance of the best interests test blurs the boundaries between negligence and battery. Limitations on children's rights to make treatment decisions for themselves impact on their potential to claim in negligence for non-disclosure and, conversely, enhance the potential relevance of the tort of battery. In paediatric cases, Montgomery raises expectations that the law is currently ill-equipped to satisfy. Tort law provides a legal incentive to disclose relevant information to children but limits the availability of a remedy.